(untitled) (Research, Society and Development, 2022)
This study aimed to evaluate the understanding of postpartum women about the baby’s oral health. This is an observational study with a cross-sectional design carried out in the maternity ward of the Integrated Health Center Amaury de Medeiros (CISAM) of the University of Pernambuco (UPE). The sample was intentionally made, consisting of 361 postpartum women from the rooming-in, between the months of April and November 2019. For data collection, a questionnaire was built aimed at the present investigation and based on other works consulted in the literature. It was found that 97.5% of the women underwent prenatal care, however only 14.4% said they had received guidance on the baby’s oral health. Therefore, a low prevalence of dental prenatal care was observed, which may reflect on the knowledge of postpartum women about the baby’s oral health. 52.6% of the interviewees said that cleaning the mouth should happen soon after the baby is born, but only 29.9% said they clean the baby’s mouth. 41% of puerperal women said it was possible for the child to grow up without caries. And 85.9% of newborns were breastfed. It is concluded, therefore, that the prevalence of guidelines on the care of the baby’s oral health during the dental prenatal period is still low, culminating in the mothers’ lack of information, which influences the children’s oral hygiene habits. With this, it is important to strengthen the role of dentists in the public network of maternal and child health care, mainly through dental prenatal care.